General practitioner views on addressing weight opportunistically in primary care: an embedded sequential mixed-methods study - Kebbe, M; Jebb, SA; Begh, R; Christian-Brown, A; Wheat, H; Farley, A; Lewis, A; Aveyard, P (Elsevier, 2021)
Objective: To assess GPs’ thoughts, feelings, and practices on providing opportunistic weight loss interventions before and after educational training and application in practice.